Healthy food : perspectives, availability and consumption - Walton, Anthony E. (Nutrition and diet research progress series., 2020)
"Healthy Food: Perspectives, Availability and Consumption first explores the pathological form of healthy eating, orthorexia nervosa. Although orthorexia nervosa cannot be found in the Diagnostic and Statistical Manual of the American Psychiatric Association, important findings suggest that orthorexia nervosa should receive wider scientific and public attention. Additionally, the current literature regarding the effects of healthy foods and early feeding practices in childhood is explored in the context of the primordial prevention of non-communicable diseases and their risk factors. This compilation also examines carrot bagasse flour and banana peel flour for their potential to be employed as functional ingredients to improve the texture, color, and flavor of raw meat products, as chorizo, or cooked meat products, as sausages. Candelilla wax oleogel is investigated for its potential to replace pork back fat lard in cooked sausages, specifically focusing on its textural profile, moisture, color, and sensory acceptance. Results indicate that candelilla wax oleogel can be employed as a fat replacement, improving the health profile of certain meat products"--